Association of the influenza A virus RNA-dependent RNA polymerase with cellular RNA polymerase II. - Engelhardt, O; Smith, M; Fodor, E (2005)
Transcription by the influenza virus RNA-dependent RNA polymerase is dependent on cellular RNA processing activities that are known to be associated with cellular RNA polymerase II (Pol II) transcription, namely, capping and splicing. Therefore, it had been hypothesized that transcription by the viral RNA polymerase and Pol II might be functionally linked. Here, we demonstrate for the first time that the influenza virus RNA polymerase complex interacts with the large subunit of Pol II via its C-terminal domain. The viral polymerase binds hyperphosphorylated forms of Pol II, indicating that it targets actively transcribing Pol II. In addition, immunofluorescence analysis is consistent with a new model showing that influenza virus polymerase accumulates at Pol II transcription sites. The present findings provide a framework for further studies to elucidate the mechanistic principles of transcription by a viral RNA polymerase and have implications for the regulation of Pol II activities in infected cells.